2017
DOI: 10.1002/jsfa.8491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo toxicity, antioxidant and immunomodulatory activities of coconut, nipah and pineapple juice vinegars

Abstract: Overall, the data suggested that not all vinegar samples cause acute and sub-chronic toxicity in vivo. Moreover, the in vivo immunity and organ antioxidant levels were enhanced, to varying extents, by the phenolic acids present in the vinegars. The results obtained in this study provide appropriate guidelines for further in vivo bioactivity studies and pre-clinical assessments of vinegar consumption. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Activation of the expression of both Glut4 and adiponectin by the coconut water vinegar treatment may help to increase the translocation and uptake of glucose in obese mice [35], increase lipid metabolism in the liver [29], and thus contribute to less lipid accumulation. Acetic acid is a major active ingredient in coconut water vinegar [18]. A previous study reported that the administration of acetic acid suppresses lipogenesis via the activation of the AMP-activated protein kinase K pathway during the metabolism of acetic acid [33].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Activation of the expression of both Glut4 and adiponectin by the coconut water vinegar treatment may help to increase the translocation and uptake of glucose in obese mice [35], increase lipid metabolism in the liver [29], and thus contribute to less lipid accumulation. Acetic acid is a major active ingredient in coconut water vinegar [18]. A previous study reported that the administration of acetic acid suppresses lipogenesis via the activation of the AMP-activated protein kinase K pathway during the metabolism of acetic acid [33].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that gallic and vanillic acids are major polyphenolic acids in vinegar [40]. Similarly to another type of vinegar, coconut water vinegar also contains gallic and vanillic acids [18]. Gallic and vanillic acids have been reported to have antioxidant, anti-inflammatory [41,42], hypolipidaemic, and liver-protective effects on HFD-induced obese rat models [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations